1997
DOI: 10.1152/jn.1997.78.6.3019
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Voltage Dependence of Inward Rectifier Currents in Spiral Ganglion Neurons

Abstract: Inward rectification was characterized in neonatal spiral ganglion neurons maintained in tissue culture. Whole cell current and voltage-clamp techniques were used to show that the hyperpolarization-activated cationic (Ih) current underlies most or all of the inward rectification demonstrated in these neurons. The average reversal potential (-41.3 mV) and cesium sensitivity were typical of that found in other neurons and cell types. What was unique about the hyperpolarization-activated currents, however, was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
57
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 50 publications
18
57
1
Order By: Relevance
“…5) is indicative of the presence of the hyperpolarization-activated currents (I h ). Previous studies have shown that spiral ganglion neurons possess I h currents with a wide range of steady state voltages of activation in spiral ganglion neurons isolated from restricted regions of the cochlea (Mo and Davis, 1997b). We wished to determine, therefore, whether NT-3 would affect the magnitude or time course of voltage changes in response to step hyperpolarizing constant-current injections that reflect the activity of the I h currents.…”
Section: Resultsmentioning
confidence: 99%
“…5) is indicative of the presence of the hyperpolarization-activated currents (I h ). Previous studies have shown that spiral ganglion neurons possess I h currents with a wide range of steady state voltages of activation in spiral ganglion neurons isolated from restricted regions of the cochlea (Mo and Davis, 1997b). We wished to determine, therefore, whether NT-3 would affect the magnitude or time course of voltage changes in response to step hyperpolarizing constant-current injections that reflect the activity of the I h currents.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic "sag" in the voltage observed for spiral ganglion neurons (Mo and Davis, 1997b) was slowed in the type II neuron (Fig. 2 F) compared with the neighboring type I (Fig.…”
Section: Basal Type II Spiral Ganglion Neuronsmentioning
confidence: 89%
“…In other cells, too, reversal potentials of this mixed cation current generally lie between -30 and -44 mV (Bal and Oertel 2000;Banks et al 1993;Chen 1997;Maccaferri and McBain 1996;McCormick and Pape 1990b;Mo and Davis 1997;Saitow and Konishi 2000;Spain et al 1987). This reversal potential reflects a permeability ratio P Na /P K of ϳ0.3 (Wollmuth and Hille 1992).…”
Section: Characteristics Of I H In Neurons From the Vcnmentioning
confidence: 98%